The Passing Fads and Emergent Trends of Project Culture in Construction Industry - Qinghua He; Jin Li; Jingyuan Wan; Zhenyu Zhang; Zhen Chen (Advances in Civil Engineering)
Project culture in construction industry is unique, distinguishing one project from others, and plays a role in the processing of construction projects. The aim of this paper is to conduct a holistic review of the extant literature and identify the future trends of project culture. The method of a systematic literature review was conducted to overview the extant articles on project culture in construction industry until 2019. After searching in ISI Web of Science, Scopus, and Google Scholar, we obtained a total number of 31 papers and refinement was made by content analysis. Four aspects were analyzed: the nature of project culture, the diagnosis of project culture, factors influencing project culture, and research focus. It provides a map of project culture from philosophy paradigms. And findings show that research on project culture was mainly from the function paradigm (the integration position) in which culture can be manipulated for better project performance. A few from nonfunction paradigm (the fragment position) stressed sense making of project culture. This study proposes a framework consisting of a hybrid function/nonfunction paradigms and diagnoses project culture from explicit and implicit aspects. These findings make a firm foundation for the exploration of project culture from multiperspectives in theory and practice.